The Kynurenine Pathway and Indole Pathway in Tryptophan Metabolism Influence Tumor Progression - Zhanhui Lu; Chengcheng Zhang; Jia Zhang; Wan Su; Guoying Wang; Zhongqi Wang (Cancer Medicine)
ABSTRACT Tryptophan (Trp), an essential amino acid, is solely acquired through dietary intake. It is vital for protein biosynthesis and acts as a precursor for numerous key bioactive compounds. The Kynurenine Pathway and the Indole Pathway are the main metabolic routes and are extensively involved in the occurrence and progression of diseases in the digestive, nervous, and urinary systems. In the Kynurenine Pathway, enzymes crucial to tryptophan metabolism, indoleamine‐2,3‐dioxygenase 1 (IDO1), IDO2, and Trp‐2,3‐dioxygenase (TDO), trigger tumor immune resistance within the tumor microenvironment and nearby lymph nodes by depleting Trp or by activating the Aromatic Hydrocarbon Receptor (AhR) through its metabolites. Furthermore, IDO1 can influence immune responses via non‐enzymatic pathways. The Kynurenine Pathway exerts its effects on tumor growth through various mechanisms, including NAD+ regulation, angiogenesis promotion, tumor metastasis enhancement, and the inhibition of tumor ferroptosis. In the Indole Pathway, indole and its related metabolites are involved in gastrointestinal homeostasis, tumor immunity, and drug resistance. The gut microbiota related to indole metabolism plays a critical role in determining the effectiveness of tumor treatment strategies and can influence the efficacy of immunochemotherapy. It is worth noting that there are conflicting effects of the Kynurenine Pathway and the Indole Pathway on the same tumor phenotype. For example, different tryptophan metabolites affect the cell cycle differently, and indole metabolism has inconsistent protective effects on tumors in different regions. These differences may hold potential for enhancing therapeutic efficacy.